Drug induced vitiligo‐like depigmentation from a CDK 4/6 inhibitor. Issue 2 (28th June 2021) - Chan, On B.; Su, John C.; Yazdabadi, Anousha; Chan, Arlene
Abstract: Ribociclib is an inhibitor of cyclin‐dependent kinases 4 and 6 (CDK 4/6) that is used in combination with an aromatase inhibitor in the first‐line setting for advanced or metastatic hormone receptor positive and human epidermal growth factor receptor 2 (HER2)‐negative breast cancer. We report two cases of drug‐induced vitiligo‐like depigmentation (DI‐VLD) associated with ribociclib. The awareness of this side effect is important given the increasing use of this drug and others with a similar mechanism of action. Abstract : Ribociclib is used in combination with an aromatase inhibitor to treat metastatic breast cancer. We report two cases of drug‐induced vitiligo‐like depigmentation (DI‐VLD) associated with ribociclib. The awareness of this side effect is important given the increasing use of this drug and others with a similar mechanism of action.